2021
DOI: 10.3390/cancers13143446
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wnt Signaling by FOX Transcription Factors in Cancer

Abstract: Aberrant activation of the oncogenic Wnt signaling pathway is a hallmark of numerous types of cancer. However, in many cases, it is unclear how a chronically high Wnt signaling tone is maintained in the absence of activating pathway mutations. Forkhead box (FOX) family transcription factors are key regulators of embryonic development and tissue homeostasis, and there is mounting evidence that they act in part by fine-tuning the Wnt signaling output in a tissue-specific and context-dependent manner. Here, I rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 147 publications
(201 reference statements)
0
17
0
Order By: Relevance
“…FOX proteins are transcription factors that regulate embryonic development and tissue homeostasis, and they are highly conserved across species. There are 44 FOX family members in humans, which are subclassified into 19 classes (A to S) based on sequence resemblance of the DNA-binding forkhead domain [ 42 ]. Functional studies of FOX have revealed that transcriptional activity differs markedly even when the domain sequences are similar.…”
Section: Downstream Wnt/β-catenin Master Genes Define the Hcc Dual Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…FOX proteins are transcription factors that regulate embryonic development and tissue homeostasis, and they are highly conserved across species. There are 44 FOX family members in humans, which are subclassified into 19 classes (A to S) based on sequence resemblance of the DNA-binding forkhead domain [ 42 ]. Functional studies of FOX have revealed that transcriptional activity differs markedly even when the domain sequences are similar.…”
Section: Downstream Wnt/β-catenin Master Genes Define the Hcc Dual Phenotypementioning
confidence: 99%
“…Evidence suggests that this close association between FOX transcription factors and the Wnt pathway contributes to cancer initiation and progression. The FOX family includes both activators and inhibitors of the Wnt pathway [ 42 ]. The Wnt pathway activators FOXM1 and FOXG1 have been reported to be expressed in HCC.…”
Section: Downstream Wnt/β-catenin Master Genes Define the Hcc Dual Phenotypementioning
confidence: 99%
“…We also investigated the underlying molecular mechanism of FOXS1 in EMT. Current literature suggests that Wnt/β-catenin pathway is essential for EMT of gastrointestinal cancer [10,11] and half of all mammalian FOX transcription factors have been assigned a role in the Wnt pathway [16], primarily in cancer cells. Given these considerations, we analyzed Wnt/β-catenin signaling pathway-related proteins in LoVo and SW620 cells 48 h after transfection with or without siRNA by Western blotting.…”
Section: Foxs1 Is a Regulator Of The Wnt/β-catenin Pathwaymentioning
confidence: 99%
“…The transcription factor forkhead box (FOX) is a family with a highly conserved winged-helix DNA-binding domain ( 1 , 2 ). FOX family members are involved in cell growth, differentiation, aging and carcinogenesis, and various regulatory and functional activities ( 3 , 4 ). From FOXA to FOXR, there are 17 gene subfamilies of FOX and more than 14 have been identified in humans ( 5 ).…”
Section: Introductionmentioning
confidence: 99%